2012
DOI: 10.3389/fpsyg.2012.00031
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Patterns of Faces do not Explain Impaired Emotion Recognition in Huntington Disease: Evidence for a High Level Mechanism

Abstract: In the current study, we aimed to investigate the emotion recognition impairment in Huntington’s disease (HD) patients and define whether this deficit is caused by impaired scanning patterns of the face. To achieve this goal, we recorded eye movements during a two-alternative forced-choice emotion recognition task. HD patients in pre-symptomatic (n = 16) and symptomatic (n = 9) disease stages were tested and their performance was compared to a control group (n = 22). In our emotion recognition task, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…That is, investigations into the neural correlates of facial emotion recognition in HD, using EEG (Croft et al, 2014), fMRI (Dogan et al, 2013), and MRI (Harrington et al, 2014), indicated an association between altered visual processing and emotion recognition. Nevertheless, a single study in HD that measured eye-movements during emotion processing did not find evidence for altered visual scanning (Van Asselen et al, 2012). This study, however, took a very different approach, compared to the approach in our study, by examining the visual scanning of faces, rather than scenes, and by measuring the scanning of specific regions of interest, rather than measuring global scanning patterns.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…That is, investigations into the neural correlates of facial emotion recognition in HD, using EEG (Croft et al, 2014), fMRI (Dogan et al, 2013), and MRI (Harrington et al, 2014), indicated an association between altered visual processing and emotion recognition. Nevertheless, a single study in HD that measured eye-movements during emotion processing did not find evidence for altered visual scanning (Van Asselen et al, 2012). This study, however, took a very different approach, compared to the approach in our study, by examining the visual scanning of faces, rather than scenes, and by measuring the scanning of specific regions of interest, rather than measuring global scanning patterns.…”
Section: Introductionmentioning
confidence: 99%
“…This study, however, took a very different approach, compared to the approach in our study, by examining the visual scanning of faces, rather than scenes, and by measuring the scanning of specific regions of interest, rather than measuring global scanning patterns. Specifically, the study looked at the number of fixations and fixation durations for the eye, nose, and mouth regions, and found no differences between the HD and control groups (Van Asselen et al, 2012). Van Asselen et al (2012) suggest that this lack of group differences in visual scanning indicates that impaired facial emotion recognition in HD may occur due to a high-level emotional mechanism, rather than due to altered visual scanning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas some studies point toward a specific deficit in recognizing facial disgust (Gray et al, ; Hennenlotter et al, ), others reveal a general impairment in recognizing negative emotions (Johnson et al, ; Labuschagne et al, ; Rees et al, ). However, intact emotion recognition competencies in premanifest HD have also been reported (Novak et al, ; Van Asselen et al, ), which might be due to variability in disease severity or gene dosage.…”
Section: Emotion Recognitionmentioning
confidence: 99%